The 1.58 Å resolution structure of the DNA‐binding domain of bacteriophage SF6 small terminase provides new hints on DNA binding. Issue 4 (2nd April 2013) - Benini, Stefano; Chechik, Maria; Ortiz Lombardía, Miguel; Polier, Sigrun; Leech, Andrew; Shevtsov, Mikhail B.; Alonso, Juan C.
<x xml:space="preserve">Abstract</x> DNA packaging in tailed bacteriophages and in evolutionarily related herpesviruses is controlled by a viral‐encoded terminase. As in a number of other phages, in the Bacillus subtilis bacteriophages SF6 and SPP1 the terminase complex consists of two proteins: G1P and G2P. The crystal structure of the N‐terminal DNA‐binding domain of the bacteriophage SF6 small terminase subunit G1P is reported. Structural comparison with other DNA‐binding proteins allows a general model for the interaction of G1P with the packaging‐initiation site to be proposed.